Violet bent backwards over the grass - Del Rey, Lana, 1985- (Simon & Schuster, 2020)
"Violet Bent Backwards Over the Grass is the title poem of the book and the first poem I wrote of many. Some of which came to me in their entirety, which I dictated and then typed out, and some that I worked laboriously picking apart each word to make the perfect poem. They are eclectic and honest and not trying to be anything other than what they are and for that reason I'm proud of them, especially because the spirit in which they were written was very authentic" --Lana Del Rey.